Challenging the responsibility of retailers towards sustainable fish supply chains - Ferreira, L.; Silva, J.; Almeida, I. (Proceedings of 3rd International Conference on BUSINESS SUSTAINABILITY, 2013 – Management, Technology and Learning for Individuals, Organisations and Society in Turbulent Environments, 2013)
Environmental concerns about the scarcity of marine resources are critical driving forces for firms aiming at preparing their supply chains for sustainability. Building up on top of previous work, this paper highlights the implementation of good practices towards sustainable operations in the seafood department, which were pursued in a retailer exploratory case. Outcomes of the adopted environmentally and socially acceptable fish retailing strategies, ranged from traceability, to self-certification and eco-labelling. Business consequences were, as follows: stronger collaboration and trust across the chain of custody, improvement of sponsors’ image and of consumers’ loyalty and, progress in the Greenpeace retailers’ evaluation ranking.